Integrative review: psychological distress among university students and correlated factors - Graner, Karen Mendes [UNESP]; Abreu Ramos Cerqueira, Ana Teresa de [UNESP] (Abrasco, 2019)
This review sought to identify risk factors and protection from psychic distress among university students. Empirical studies were analyzed in the Web of Science, Medline and Scopus databases. A total of 1,375 articles were located, and after the exclusion criteria were applied, 37 articles made up the final sample, most of which were cross-sectional studies published in the last five years, in developed countries and with students in the health area. The most frequently used instruments for psychic distress screening were the General Health Questionnaire and the Self Reporting Questionnaire, which identified a prevalence of between 18.5% and 49.1% and, as risk factors, conditions related to academic life (24) and to health (22). Twelve studies identified as protective factors: given coping strategies, sense of coherence, self-efficacy, vigor, self-esteem, resilience, among other psychological conditions. This review singles out directions for possible interventions that could contribute to the well-being of students and to stimulate more positive experiences in the educational environment.
Keywords: Psychic distress; Mental disorders; Students; Risk factors; Review